2020
DOI: 10.3389/fbioe.2020.01010
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Exosome Mimicking Nanoparticles for Tumor Combinatorial Chemo-Photothermal Therapy

Abstract: The development of biomimetic nanoparticles with functionalities of natural biomaterial remains a major challenge in cancer combination therapy. Herein, we developed a tumor-cell-derived exosome-camouflaged porous silicon nanoparticles (E-MSNs) as a drug delivery system for co-loading ICG and DOX (ID@E-MSNs), achieving the synergistic effects of chemotherapy and photothermal therapy against breast cancer. Compared with ID@MSNs, the biomimetic nanoparticles ID@E-MSNs can be effectively taken up by the tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…In their research, tumor-derived exosomes were mixed with mesoporous silica nanoparticles (MSNs) loaded with DOX and ICG then exosome-camouflaged MSNs (ID@E-MSNs) was constructed through extrusion. Likewise, their outcomes demonstrated that ID@E-MSNs could produce hyperthermia to collapse nano-vehicles and accelerate drug release, achieving effective chemo-photothermal therapy under 808 nm NIR irradiation [ 70 ]. In short, all the researches above indicate that engineered EVs as delivery platforms perform strong load capacity and good biocompatibility, which means they have great potential in combinational chemo-photothermal therapy.…”
Section: Engineered Evs For Chemotherapy-related Combination Therapymentioning
confidence: 99%
“…In their research, tumor-derived exosomes were mixed with mesoporous silica nanoparticles (MSNs) loaded with DOX and ICG then exosome-camouflaged MSNs (ID@E-MSNs) was constructed through extrusion. Likewise, their outcomes demonstrated that ID@E-MSNs could produce hyperthermia to collapse nano-vehicles and accelerate drug release, achieving effective chemo-photothermal therapy under 808 nm NIR irradiation [ 70 ]. In short, all the researches above indicate that engineered EVs as delivery platforms perform strong load capacity and good biocompatibility, which means they have great potential in combinational chemo-photothermal therapy.…”
Section: Engineered Evs For Chemotherapy-related Combination Therapymentioning
confidence: 99%
“…In agreement with the recent observation that EVs derived from autologous cancer cells have potential tropism to the TME making them competitive delivery vehicles with enhanced anticancer efficacy [ 254 ], Tian et al developed tumour-cell-derived exosome-camouflaged porous silicon nanoparticles (E-MSNs) as a drug delivery system for indocyanine (ICG) and doxorubicin (ID@E-MSNs). This approach showed synergistic effects of chemotherapy and photothermal therapy against BC [ 248 ].…”
Section: Clinical Applications Of Extracellular Vesicles In Therapy Resistancementioning
confidence: 99%
“…Table 2 summarizes different examples of NPs coated with EVs, their coating mechanisms, and the unique features of this strategy for drug delivery applications. [105,106,119,137,[146][147][148][149][150][151][152][153][154][155]…”
Section: Evs-mesoporous Silica Npsmentioning
confidence: 99%